Evaluation of natural products bioactivity in cardiovascular diseases utilizing zebrafish models: a comprehensive review - Wang, Yiming; Meng, Xiang; Song, Xuting; Wang, Lulu; Meng, Xianghe; Du, Xiaoya; Yusupov, Ziyoviddin; Tojibaev, Komiljon; Wang, Yunpeng; He, Min; Sun, Mengmeng (Frontiers in Pharmacology, 2025)
Cardiovascular diseases (CVDs) are a major global health challenge, significantly impacting public health and healthcare systems. Ethnopharmacological remedies and botanical medicines are widely used for the prevention and treatment of CVDs due to their multi-component, multi-target properties. Understanding the mechanisms of these natural products is essential for developing safe and effective therapies. The zebrafish model, an emerging tool in experimental pharmacology, has been increasingly used to evaluate the pharmacological activities of natural products. This review focuses the use of zebrafish models to test the prevention and treatment effects of various CVDs, and to investigate the inhibition of hyperlipidemia, thrombosis, the progress of heart failure, and the promotion of angiogenesis and toxicity. Emphasizing its experimental advantages-including the transparency characteristics of the body, its applicability to the analysis of multiple samples, and its support for real-time monitoring-aims to reveal its potential value in combining traditional cognition with contemporary pharmacological testing capabilities. The literature summary provides strong evidence for the cognitive improvement of the zebrafish system in clarifying the efficacy of natural ingredients in the cardiovascular field.